The impact of children on Australian couples' wealth accumulation - Bawa, Sherry; Dockery, Alfred Michael (Bankwest Curtin Economic Centre, Curtin Business School, 2013)
Existing estimates of the cost of raising children mainly focus on what parents spend on their children. This paper challenges the conceptual basis for this approach, and instead investigates how the presence of children impacts upon couples’ wealth accumulation using the life-cycle approach and Australian household panel data. Both the results presented here for Australia and those contained in the existing literature suggest that raising a family has a very small impact upon wealth accumulation relative to the ‘cost’ implied from expenditure based estimates. In reconciling these highly divergent estimates, we argue the estimates from the wealth approach make more intuitive sense on a number of fronts, with implications for families and policy.
Bankwest Curtin Economics Centre Working Paper
Bankwest Curtin Economics Centre Working Paper series
Keywords: Children; Income & Finance -- Financial Management (inc Budgeting); Income & Finance -- Wealth; Families; Activities -- Leisure and lifestyle; Childhood and child development; Families and relationships; Income, wealth and finances; Children; Income & Finance; Families; Activities; Leisure and lifestyle; Financial Management (inc Budgeting); Wealth; Families and relationships; Income, wealth and finances; Childhood and child development